TINJAUAN YURIDIS LEGALITAS PENYADAPAN KOMUNIKASI MELALUI TELEPON SEBAGAI SUATU ALAT BUKTI DALAM PERKARA TINDAK PIDANA KORUPSI - Romy Irawan (Universitas 17 Agustus 1945 Samarinda, 2014)
ABTRACT The term telematics legal embodiment of the telecommunications law , Media Law and Information Technology Law , other terms used are Information Technology Law ( Law of Information Technology , ) the law of cyberspace ( virtual word law ) and the law mayantara . The term birth because the activities carried out through a system of computer networks and communication systems both locally and globally ( Internet ) by using information technology and communications or transactions electronically , particularly in investigations and matters related to the delivery of information . Communication and interaction or electronically , particularly in terms of evidence and matters relating to legal actions carried out through electronic systems .One of the growing use of technology areas that we often hear tapping or better known as intresepsi , with various controversies that followed . Occurrences intercepts as specific rules actually noble , normatively known in 1997 when the enactment of Law Psychotropic Substances ( Law No. 5 of 1997 ) with effect from March 11, 1997 and Narcotics Law Undnag long ( Law No. 22 of 1997 which entered into force on 1 September 1997 ).In Act No. 11 of 2008 on Information and Electronic Transactions ( ITE Law ) in Article 31 paragraph ( 1 ) also stated that the ban on people who knowingly and looks or unlawful interception or eavesdropping over the conduct of electronic and information or documents electronically in a computer or electronic system specific and belong to someone else this provision refers to Article 31 paragraph ( 3 ) which states